(untitled) (Damascus University Journal for engineering sciences, 2024)
Rail transport has unequivocal environmental and economic sustainable advantages in large scale container transportation. container loading is an important part of railway transportation system. As the improvement of railway service in every sea port would have an impact on production operations on the one hand, and on the time and cost of transporting containers on the other hand, especially when transporting to dry ports. This paper focuses on studying options for benefiting from the mechanism of transporting containers from Lattakia port to dry ports using railways, by suggestion two methods for the transportation process. In the end, the results of the analysis of container transportation by adopting rail transportation show that the direct shipment of containers from ship to rail can significantly reduce handling time and costs compared to additional handling movements and dwell time of containers in yards in the case of indirect shipment.